2007
DOI: 10.1097/mao.0b013e3180a726c9
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic Emissions in Early Noise-Induced Hearing Loss

Abstract: The DP-gram is not significantly correlated with PTaud and cannot be used as an objective measure of pure-tone thresholds in early NIHL. Medial olivocochlear reflex strength before the beginning of chronic exposure to occupational noise has no relation to individual vulnerability to NIHL. Although TEOAEs changes after 1 year showed high sensitivity in predicting NIHL after 2 years of exposure, they cannot be recommended as an efficient screening tool due to high false-positive rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 20 publications
3
43
2
7
Order By: Relevance
“…More recently, novel methods to assess hearing loss as a result of noise exposure are being employed, such as otoacoustic emissions that can predict lesions prior to their being disclosed by a clinical audiometry, and these are used more frequently to assess exposure to workrelated noise 29 . Studies concerned with exposure to urban recreational or environmental noise are scarce in Mexico, but one study found high levels of street noise during day time, related to automotive traffic 30 .…”
Section: Audiometric Findingsmentioning
confidence: 99%
“…More recently, novel methods to assess hearing loss as a result of noise exposure are being employed, such as otoacoustic emissions that can predict lesions prior to their being disclosed by a clinical audiometry, and these are used more frequently to assess exposure to workrelated noise 29 . Studies concerned with exposure to urban recreational or environmental noise are scarce in Mexico, but one study found high levels of street noise during day time, related to automotive traffic 30 .…”
Section: Audiometric Findingsmentioning
confidence: 99%
“…Earlier human studies were not well-geared to reveal whether MOCR strength is predictive of permanent NIHL in humans. In a prospective study, Shupak et al (2007), using a TEOAE-based MOCR test, found no evidence that MOCR strength predicted PTS in humans. However, their MOCR test was possibly confounded with crossover noise from the headphones, and the MEMR could have been activated by the high (65 dB SPL) contralateral noise elicitor (e.g., Guinan et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, otosclerosis involvement of the cochlea is associated with decreased counts and depressed motility of the outer hair cells [45,46] . Limited derangement of the outer hair cells might attenuate and ablate OAE response before sensorineural hearing loss becomes apparent in behavioral audiometry [47] .…”
Section: Discussionmentioning
confidence: 99%